PENGEMBANGAN MEDIA VIDEO POWTOON BERBASIS PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Ovi Haryani; Yeni Erita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the lack of variety in learning media used in the learning process. Therefore, learning media is needed that is tailored to students' preferences. One of them is the development of Powtoon video media in science learning. This research aims to produce learning media in the form of animated videos for science and science learning in Class V Elementary Schools that are valid and practical. This research is Research & Development research, the development model used is the ADDIE model. The ADDIE development model consists of five stages, namely analysis, design, development, implementation, evaluation. This research was conducted at SDN SDN 02 Campago Guguk Bulek and SDN 17 Manggis Ganting. The designed media is validated by validators using a validation sheet in the form of a questionnaire. This product validation consists of material experts, language experts and media experts. Then it was tested in Class V at SDN 02 Campago Guguk Bulek and SDN 17 Manggis Ganting to find out the practicality of the media being developed. The research results showed that learning media had a media validity level of 82.5%, material validity of 86.25%, and linguistic validity of 91% in the very valid category. The practicality test results of teacher responses received an average score of 92% and the practicality score of students received an average score of 94% in the very practical category. Thus, it can be concluded that the learning media in the form of animated powtoon videos for science and science learning in Class V Elementary School has been declared valid and practical.